Plan de negocios, mediante la aplicación de la metodología de Canvas, para proponer la creación de la hostería "posada de Jumandi", dirigida a personas de la tercera edad, en el cantón Archidona - Shiguango Shiguango, Lenin Diego (2016)
The study proposes the creation of the inn “Jumandi Inn" located in Archidona Town, Napo Province, in order to strengthen tourism development in the area, offering a different service according to the needs of adult tourist people, with facilities and services that count with requirements of this tourist segment. The general objective is to design a business plan, by applying the CANVAS methodology, for which the current situation assessment of the study area was conducted, the business plan was implemented with the CANVAS methodology and finally its creation is established the inn for the effect was used, primary and secondary sources of information. This research corresponds to a non-experimental design; It is based on descriptive, documentary and field research. I also used techniques such as observation, surveys and interviews. Market research was conducted in order to determine the demand in the town, which surveys 116 of a total of 29.100 tourists that were conducted, the results indicate that the 80 % of respondents believe that it should build an inn that aims at older people. The financial results of the investigation indicate the economic feasibility; to do different economic parameters (revenues, expenditures, NPV, IRR, cost / benefit, etc.) in order to obtain results of economic profitability of the project were reviewed. With all the information collected in the stages of the project was concluded, the feasibility of the creation of the inn.